Dipeptidyl peptidase 4 (DPP-4) inhibitors and cardiovascular outcomes in patients with type 2 diabetes mellitus (T2DM): a systematic review and meta-analysis - Dan Liu; Biao Jin; Wei Chen; Peng Yun (BMC, 2019)
Abstract Background Dipeptidyl peptidase 4 (DPP-4) inhibitors are newer oral anti-diabetic agents which have been approved by the Food and Drug Administration for the treatment of patients with type 2 diabetes mellitus (T2DM). In this analysis, we aimed to systematically compare the cardiovascular outcomes associated with DPP-4 inhibitors versus non-DPP-4 inhibitor users. Methods All English publications that compared the use of DPP-4 inhibitors and that reported cardiovascular outcomes in patients with T2DM were searched using specific terms. Studies were included if they satisfied the following inclusion criteria: They were randomized trials or observation cohorts/registries comparing DPP-4 inhibitors use in patients with T2DM; The studies included a large sample size of participants; And they reported cardiovascular outcomes as their main endpoints. RevMan 5.3 was used to analyze the data, and odds ratios (OR) with 95% confidence intervals (CI) were used to represent the results. Results A total number of 157,478 participants with T2DM were included. Seventy-six thousand and twenty six patients were assigned to the DPP-4 inhibitor group whereas 81,452 patients were assigned to the control group. Results of the current analysis showed that during a mean follow-up time period ranging from 52 to 152 weeks, the primary endpoint (cardiovascular death/non-fatal myocardial infarction (MI)/non-fatal stroke) was not significantly different in the treatment of T2DM patients with versus without DPP-4 inhibitors (OR: 0.95, 95% CI: 0.86-1.04; P = 0.26). Cardiovascular death (OR: 1.00, 95% CI: 0.90-1.10; P = 0.93), stroke (OR: 1.03, 95% CI: 0.89-1.18; P = 0.72), MI (OR: 0.97, 95% CI: 0.88-1.07; P = 0.59), all-cause mortality (OR: 0.84, 95% CI: 0.59-1.18; P = 0.31), hospitalization for cardiovascular complications (OR: 1.02, 95% CI: 0.96-1.09; P = 0.45) and hospitalization specifically for heart failure (OR: 1.05, 95% CI: 0.90-1.23; P = 0.55) were also similarly manifested in both groups. Conclusion The current analysis showed that treatment with DPP-4 inhibitors did not significantly increase cardiovascular outcomes in these patients with T2DM indicating that those drugs might be safe to use in terms of cardiovascular events.